PENATALAKSANAAN KETOASIDOSIS DIABETIK (KAD) - Gotera, Wira; Agung Budiyasa, Dewa Gde (journal of internal medicine, 2010)
Diabetic Ketoasidosis (DKA) is metabolic disturbance disorder that be signed by trias hyperglycemia, acidosis, andketosis, which one of very serious acute metabolic complication of diabetes mellitus. In Indonesia the incidence was not sohigh compare than the western countries, but the mortality is still high. In young age the mortality can be prevented by earlydiagnosis, rational and prompt treatment according to it!s pathophysiology. Succesfull of DKA treatment needs correction ofdehidration, hyperglycemia, acidosis, and electrolyte disturbance, identiÞ cation of comorbid precipitation factor, and the mostimportant one was continue monitoring. The treatment were adequate of ß uid therapy, sufÞ cient insulin theraphy, therapy ofpotassium, bicarbonate, phosphat, magnesium, hyperchloremic condition, and antibiotic administration according to indication.The important one was also awarness for therapy complications so that the therapy not to make worsening condition of thepatients.